PENGARUH PERENCANAN PAJAK, AKTIVA PAJAK TANGGUHAN, BEBAN PAJAK TANGGUHAN DAN UKURAN PERUSAHAAN TERHADAP EARNING MANAGEMENT - Saijan Saijan (Universitas Medan Area, 2020)
This research is to identify and to test the effect of tax planning, deferred tax assets, deferred tax expense and company measurement towards the earning management of Indonesia capital market. Data in-used in this research is originated from the financial statements that has heen audited by the property companies, real estate and building construction which have been registered in Indonesia Syariah Stock Index by the year of 2014-2018. Sample determination is done by the purposive sampling method. There are eight out of 66 companies that will be analyzed with multiple linear regressions. The analysis result shows that the tax planning and deferred tax assets have the positive and significant impacts to the companies that practice the earning management, whereas the deferred tax expense and company measurement are not resulting in significant impact.